Accuracy of intraoperative frozen section for the evaluation of ovarian neoplasms: an institutional experience. Issue 1 (December 2016) - Hashmi, Atif; Naz, Samreen; Edhi, Muhammad; Faridi, Naveen; Hussain, Syed; Mumtaz, Shazia; Khan, Mehmood
Abstract Background Ovarian neoplasms are a heterogeneous group of tumors including surface epithelial, germ cell and sex cord stromal tumors with a subset having low malignant potential (borderline tumors). While the surgical management plan differs in different categories of tumors, preoperative diagnosis is seldom available. In these circumstances, the role of frozen section becomes invaluable. In the current study, we aimed to evaluate the accuracy of the frozen section of ovarian tumors in our setup. Methods It was a retrospective study involving 141 cases of ovarian tumors undergoing surgical resection with frozen section evaluation from January 2009 to December 2014. After gross examination, one to five blocks were prepared on the frozen section depending upon the size of the specimen. After frozen section reporting, specimens were processed routinely for final paraffin section evaluation. Results of frozen and paraffin sections were categorized in benign, borderline, and malignant, and accuracy of frozen section was determined. Results Out of 141 cases, 107 were diagnosed as benign on final (paraffin) examination, while 6 were borderline and 28 were malignant. Out of 107 benign cases, 45 were non-neoplastic cystic lesions of the ovary including endometriotic, follicular, and corpus luteal cysts. The most common benign neoplastic tumor was mature cystic teratoma (20 cases) followed by mucinous cystadenoma (19 cases), serous cystadenoma (14 cases), sex cord stromal tumors (8 cases), and Brenner tumor (1 case). Among borderline cases, four cases were serous and two of mucinous neoplasms. The most common malignant neoplasm was serous carcinoma (11 cases) followed by mucinous carcinoma (6 cases). The overall accuracy of frozen section diagnosis is above 99 %. The sensitivity and specificity for benign tumors were found to be 100 and 97 %, respectively. The sensitivity and specificity for borderline tumors was 83 and 99 %, respectively, while for malignant tumors, it was 96 and 100 %, respectively. Conclusions We found a high sensitivity and specificity of frozen section for the diagnosis of ovarian tumors and to determine its malignant potential. Therefore, it should always be used when the preoperative diagnosis is not definite to govern extent of surgical resection. However, under-diagnosis can occur in tumors of borderline category which can be minimized by increased sampling on the frozen section.